Penyuluhan Penanggulangan Penyakit Ikan Bagi Pembudidaya Nila Kolam Terpal Di Desa Kramajaya, Lombok Barat - Muahiddah, Nuri; Fariq Azhar; Muhammad Marzuki; Andre Rachmat Scabra; Rangga Idris Affandi; Sumsanto, Muhammad; Yuliana Asri; Wastu Ayu Diamahesa; Damai Diniariwisan (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
Fish diseases are one of the primary challenges faced by fish farmers, including tilapia fish farmers using tarpaulin ponds in the village of Kramajaya, West Lombok. Fish diseases can lead to significant losses in the fish farming business. Therefore, education on the management of fish diseases is essential to assist farmers in safeguarding their fish stocks and ensuring the success of their aquaculture endeavors. This endeavor aims to provide education to tilapia fish farmers using tarpaulin ponds in Kramajaya village, West Lombok, regarding the management of fish diseases. The education methods employed encompass the dissemination of information about the causes, symptoms, prevention, and treatment of fish diseases, along with aquaculture practices that can help mitigate the risk of diseases. The results of this education show an improvement in the knowledge of fish farmers regarding the management of fish diseases. They become more aware of the signs of fish diseases and are capable of taking appropriate preventive measures. Furthermore, they also understand the importance of maintaining water quality and the cleanliness of tarpaulin ponds as disease prevention measures. This education also provides a better understanding of the use of medications and proper medical actions in case fish diseases occur. Consequently, fish farmers can respond more promptly and effectively to fish diseases, which, in turn, can enhance the production of tilapia fish and the overall success of their aquaculture businesses.